Sistem Pakar Diagnosa Penyakit Gigi dengan Metode Bayesian Network Berbasis Website - Yunda Aisyah; Fitri Bimantoro; Budi Irmawati (Journal of Computer Science and Informatics Engineering (J-Cosine), 2019)
Teeth serve to chew food, say words clearly, form a harmonious face and for a better appearance. Healthy teeth and gums will make it easy to eat well and enjoy good food. There are some problems that can affect oral health, but good care will make the teeth and gums strong. Lack of public awareness of maintaining dental health can cause major problems later on. In this case, an expert system tool for diagnosing dental diseases will be made using the website-based Bayesian Network method. The initial step in this study was to collect data, such as data on dental disease, data on dental disease symptoms and the weight of each symptom of dental disease used. The data was obtained from three dental disease doctors in three health centers in East Lombok. After getting the data, then calculating the weights for each symptom, the results of the calculation will be summed then divided by the number of symptoms suffered by the patient. The results of these calculations can be consulted by a dental specialist.